The Relationship Between Leg Muscle Explosive Power And Limb Length On The Results Of Flop Style High Jump In Jakarta State Athletic KOP Students - Osa Miftahul Firdaus; Bambang Kridasuwarso; Bambang Sujiono (UNIVERSITAS NEGERI MAKASSAR, 2023)
This study aims to determine whether there is a relationship between leg muscle explosive power and leg length on high jump results in KOP athletics students of Jakarta State University. The design of this study is a quantitative study that uses a series of tests, namely the measurement of leg length, vertical jump test and flop style high jump test. There were a total of 20 subjects studied and only 18 met the instrument test. Data processing using SPSS version 20 with Correlation found a correlation result of leg muscle explosive power of 0.673 and a significance value of 0.000 where the significance value was smaller than 0.05 indicating a strong relationship between leg muscle explosive power and high jump results. Then based on the results of the correlation test the correlation result of the length of the limb of 0. 818 and the significance value of 0.000 where the significance value was smaller than 0.05 The variable correlation value shows a positive value and shows a very strong relationship between leg length and high jump results. Then based on the results of the f test, it is known that the significance value in this f test has a value of 0.000 less than 0.05 so it can be concluded that there is a relationship between the explosive power of the leg muscles and the length of the tugkai together with the high jump results of KOP athletics students of Jakarta State University.